Rheological and textural properties of sodium reduced salt soluble myofibrillar protein gels containing sodium tri-polyphosphate - Çarkcioğlu, Emine; Rosenthal, Andrew J.; Candoğan, K. (Wiley, 2016)
The effect of partial replacement of NaCl (50%) with KCl in the presence of sodium tri-polyphosphate (STPP) on the cooking loss (CL), water-holding capacity (WHC), rheological and textural properties of salt soluble myofibrillar proteins (SSMP) gels was investigated. KCl substitution, either alone or in combination with STPP, was found worse than NaCl alone in terms of elasticity of the gels (G′). Both KCl and STPP reduced the CL of the gels. While the gels with replacement of NaCl with KCl had lower (P < 0.05) WHC, addition of STPP to this gels gave rise to similar (P > 0.05) WHC to only NaCl added gels. Substitution of NaCl with KCl resulted in a decrease in hardness of gels whereas STPP addition improved the hardness. Results obtained from the present study suggest that substitution 50% of NaCl with KCl in presence of STPP would be a sound salt reduction alternative in meat systems.